2023
DOI: 10.1037/pspp0000417
|View full text |Cite
|
Sign up to set email alerts
|

The impact of unemployment on cognitive, affective, and eudaimonic well-being facets: Investigating immediate effects and short-term adaptation.

Abstract: While long-lasting declines in life satisfaction following unemployment have been well documented, evidence on the impact of unemployment on affective and eudaimonic well-being is scarce. Moreover, most existing studies relied on yearly panel data and were unable to separate the immediate effects of entering unemployment from prospective effects occurring before individuals become unemployed. The present study identified the immediate effects of entering unemployment on cognitive, affective and eudaimonic well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 119 publications
4
14
0
Order By: Relevance
“…In terms of unemployment, extensive research showed that entering unemployment is on average associated with declining life satisfaction (Clark et al, 2008;Lawes, Hetschko, Schöb, et al, 2022;Luhmann et al, 2012). Moreover, becoming unemployed has been shown to be related to decreases in satisfaction with one's income (Chadi & Hetschko, 2017;Lawes, Hetschko, Schöb, et al, 2022) and social life (Powdthavee, 2012). Contrarily, positive effects of unemployment were found in terms of increased satisfaction with one's leisure time and family life (Chadi & Hetschko, 2017).…”
Section: Unemployment and Subjective Well-beingmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of unemployment, extensive research showed that entering unemployment is on average associated with declining life satisfaction (Clark et al, 2008;Lawes, Hetschko, Schöb, et al, 2022;Luhmann et al, 2012). Moreover, becoming unemployed has been shown to be related to decreases in satisfaction with one's income (Chadi & Hetschko, 2017;Lawes, Hetschko, Schöb, et al, 2022) and social life (Powdthavee, 2012). Contrarily, positive effects of unemployment were found in terms of increased satisfaction with one's leisure time and family life (Chadi & Hetschko, 2017).…”
Section: Unemployment and Subjective Well-beingmentioning
confidence: 99%
“…Panel studies utilizing retrospective assessments of AWB indicated that unemployment has negative effects on sadness, happiness, and anxiety (von Scheve et al, 2017) as well as mood (Hentschel et al, 2017). Contrarily, studies that measured AWB with the experience sampling method (ESM, Hektner et al, 2007) or the day reconstruction method (DRM, Kahneman et al, 2004), which are less prone to recall biases compared to classical questionnaires, found no systematic effects of unemployment on various AWB facets (Dolan et al, 2017;Hoang & Knabe, 2021;Lawes, Hetschko, Schöb, et al, 2022;Wolf et al, 2022).…”
Section: Unemployment and Subjective Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Lawes et al (2022) were specifically interested in the immediate effect of unemployment on well-being and estimated month-to-month changes. However, the data they analyzed differed from those of most other studies: they used a high-frequency panel where individuals were indeed interviewed at monthly intervals.…”
Section: Literature Reviewmentioning
confidence: 99%